Transportation and electricity systems integration via electric vehicle charging-as-a-service: A review of techno-economic and societal benefits. (April 2023) - Trinko, David; Horesh, Noah; Porter, Emily; Dunckley, Jamie; Miller, Erika; Bradley, Thomas
Abstract: In support of global decarbonization efforts, the adoption of electric vehicles is proceeding rapidly across transportation sectors, population groups, and regions. However, access to electric vehicle charging infrastructure remains sparse and inequitable, and technical, economic, and procedural challenges have encumbered its expansion. Charging-as-a-service, which can mitigate cost and effort risks of charging equipment ownership, adds a means of meeting many of these challenges. As charging-as-a-service has not been analyzed or addressed in the scholarly literature, we synthesize media, marketing, and analogous scholarly publications to categorize and describe the functions asserted by existing charging-as-a-service vendors. We demonstrate and quantify the benefits of many of these functions via four example business cases, sited at a detached residence, a multi-unit dwelling, a consumer-facing business, and a commercial fleet depot. Outcomes show that savings and revenues realized via charging-as-a-service can reduce charging costs, beneficially shape grid loads, and make charging installation economical where it otherwise would not be. Discussion highlights the need to deploy charging-as-a-service in cooperation with initiatives promoting societal benefits, including charging access equity. Graphical abstract: Highlights: First review of the purpose and functions of EV charging-as-a-service (ChaaS). ChaaS enables transfer of EV charging operation and ownership burdens. Simplifies negotiating the requirements of transportation and electricity systems. Functions and benefits are demonstrated in residential and commercial business cases. ChaaS should be deployed to advance societal interests, e.g. charging access equity.